Effect of Hydrogen Bonds on Crystallization Kinetics of Aqueous Solutions of Cryoprotective Agents - Osetsky, Aleksandr I.; Sevastyanov, Stanislav S. (Problems of Cryobiology and Cryomedicine, 2016)
The temperature dependences of volume for aqueous solutions of DMSO and glycerol under various concentrations during their cooling down to –150°C and subsequent heating up to 25°C were studied in details in this paper. It was shown that within the range of 30–70% weight concentrations of cryoprotective substances these dependences differed greatly at cooling stages and during subsequent thawing. It has been also found that within the studied concentration range there was a sharp increase in volume for glycerol solutions when heated above the glass transition temperature, and vice versa, a sharp reduction in DMSO solution volume. It has been noted that the observed volume effects fit well within the concept of cluster crystallization of cryoprotective solutions, taking into account a weak HB-interaction between the components. On the basis of the findings the structure of the formed cluster particles was analyzed. It has been shown that the surface layers from the molecules of cryoprotective agent surrounding ice microcrystals can be of either crystalline or amorphous structure. The effect of these differences on protective properties of cryoprotectants was examined. Probl Cryobiol Cryomed 2016; 26(3): 199–212